DOMESTIC VIOLENCE AGAINST WOMEN DURING THE COVID-19 PANDEMIC IN BALI: A HINDU SOCIOLOGICAL PERSPECTIVE ON RELIGIOUS CULTURE AND GENDER RELATIONS - I Nyoman Alit Putrawan (UHN I Gusti Bagus Sugriwa Denpasar, 2026)
Domestic violence against women constitutes a significant social and ethical issue that intensified during the COVID-19 pandemic, particularly in culturally and religiously structured societies such as Bali. The pandemic generated economic instability, social restrictions, and increased domestic pressures, which contributed to the escalation of violence within households. Within the Balinese Hindu context, this phenomenon is closely linked to religious culture, gender relations, and the persistence of patriarchal values embedded in the patrilineal system. This study aims to analyse the causes and dynamics of domestic violence against women during the pandemic in Bali from a Hindu sociological perspective, with particular attention to the interaction between religious values, cultural practices, and gender inequality. This research adopts a qualitative design using a narrative review method. Data were collected from scholarly journal articles, institutional reports, and academic publications published between 2019 and 2023, accessed through databases such as Scopus, EBSCO, and Google Scholar. The analysis is informed by sociological theories of gender and patriarchy, alongside key Hindu concepts, namely dharma and Tri Hita Karana, to provide a culturally grounded interpretation. The findings indicate that domestic violence during the pandemic is influenced by both internal and external factors. Internal factors include psychological stress, emotional instability, and past trauma, while external factors involve economic hardship, social restrictions, increased domestic workloads, and entrenched patriarchal norms. From a Hindu sociological perspective, such conditions reflect a disruption of ethical balance, particularly a deviation from dharma and a breakdown of harmony within the Tri Hita Karana framework, especially in the pawongan (human relations) dimension. At the same time, religious values, when interpreted progressively, have the potential to serve as a moral foundation for preventing violence and promoting gender justice. In conclusion, domestic violence against women in Bali during the COVID-19 pandemic is not solely a socio-economic issue but also a cultural and religious phenomenon. Addressing this problem requires not only legal and economic interventions but also the rearticulation of Hindu values to support equality, dignity, and harmonious social relations.